2022
DOI: 10.1111/aphw.12362
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, psychological distress, and somatic symptoms among women engaged in sex work in China

Abstract: Women engaged in sex work (WSW) in China encounter numerous disadvantages (e.g., exposure to violence) and have substantial risk for psychological distress and somatic symptoms. Intervention literature has attended to mindfulness, which is a protective factor for psychological outcomes, and its influences can further improve physical health. However, mindfulness has not been well studied in WSW. We aimed to examine the association among mindfulness, psychological distress, and somatic symptoms among Chinese WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Significantly lower rates of depression in depression were reported from a study in China (37) and in Malawi (38). The study in Malawi reported a 9% prevalence rate of probable depression while the study in China reported depression among 8% of the FSWs.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Significantly lower rates of depression in depression were reported from a study in China (37) and in Malawi (38). The study in Malawi reported a 9% prevalence rate of probable depression while the study in China reported depression among 8% of the FSWs.…”
Section: Discussionmentioning
confidence: 65%
“…In the global literature different anxiety and depression prevalence rates were reported among FSWs where some were higher, others comparable and some others were lower than the rate found in our study. For instance, the rates of depression levels range from 9% among FSWs in China (Tam et al, 2022) to 80.9% among FSWs in South Africa (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation